TEACHING LEGAL ENGLISH VOCABULARY AT LAW UNIVERSITIES - Ashurov Jahongir (Journals Park Publishing, 2023)
This study presents a detailed examination of the methods and strategies employed in teaching legal English vocabulary at law universities. The effective acquisition of legal English vocabulary is crucial for law students and professionals to excel in their field, as it enables accurate comprehension and communication within the legal domain. This article investigates the best practices, challenges, and innovative approaches in teaching legal English vocabulary, aiming to provide valuable insights for educators and curriculum designers in law universities.
Keywords: Legal English, task-based approach, pedagogical framework, language acquisition, vocabulary acquisition, legal practice preparation, problem-solving skills.